Implementing result-based agri-environmental payments by means of modelling - Bartosz Bartkowski; Nils Droste; Mareike Ließ; William Sidemo-Holm; Ulrich Weller; Mark V. Brady (Helmholtz-Zentrum für Umweltforschung (UFZ), 2019)
From a theoretical point of view, result-based agri-environmental payments are clearly preferable to action-based payments. However, they suffer from two major practical disadvantages: costs of measuring the results and payment uncertainty for the participating farmers. In this paper, we propose an alternative design to overcome these two disadvantages by means of modelling (instead of measuring) the results. We describe the concept of model-informed result-based agri-environmental payments (MIRBAP), including a hypothetical example of payments for the protection and enhancement of soil functions. We offer a comprehensive discussion of the relative advantages and disadvantages of MIRBAP, showing that it not only unites most of the advantages of result-based and action-based schemes, but also adds two new advantages: the potential to address trade-offs among multiple policy objectives and management for long-term environmental effects. We argue that MIRBAP would be a valuable addition to the agri-environmental policy toolbox and a reflection of recent advancements in agri-environmental modelling.
Keywords: Q18; Q24; Q52; Q58; 330; agriculture; agri-environmental policy; governance; incentives